The nature of multiple procurement rules and the policy issues arising from multiplicity of rules: a case study of Ghana - Borson, Fred (2016)
Many African countries such as Ghana have adopted rules and procedures that regulate the conduct of public procurement. These developing countries usually rely on foreign aid, which is disbursed through public procurement, to undertake major development projects. However, unreliable domestic systems contribute to the motivation of donors who usually require beneficiary countries to apply procurement rules and procedures set out by the donor for the implementation of development projects funded by the donor. Different rules of donors are applicable to procurement in addition to existing rules under the domestic regime, which results in the application of multiple procurement rules.